2019
DOI: 10.1158/1940-6207.capr-18-0443
|View full text |Cite
|
Sign up to set email alerts
|

“A Natural Progression”: Australian Women's Attitudes About an Individualized Breast Screening Model

Abstract: Individualized screening is our logical next step to improve population breast cancer screening in Australia. To explore breast screening participants' views of the current program in Victoria, Australia, examine their openness to change, and attitudes toward an individualized screening model, this qualitative work was performed from a population-based breast screening cohort. This work was designed to inform the development of a decision aid to facilitate women's decisions about participating in individualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(110 citation statements)
references
References 34 publications
6
104
0
Order By: Relevance
“…A recent quantitative survey found that only 57% of women surveyed in five European countries stated that they would consider less cancer screening if they were at lower than average genetic risk, 12 and qualitative research from Australia found that women feel a strong emotional connection to current methods of breast screening. 13 A relevant caveat to this finding is that a greater number of screening risks were presented compared with benefits. This is consistent with the existing NHS screening information leaflet, 4 have increased preferences for reduced-frequency (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…A recent quantitative survey found that only 57% of women surveyed in five European countries stated that they would consider less cancer screening if they were at lower than average genetic risk, 12 and qualitative research from Australia found that women feel a strong emotional connection to current methods of breast screening. 13 A relevant caveat to this finding is that a greater number of screening risks were presented compared with benefits. This is consistent with the existing NHS screening information leaflet, 4 have increased preferences for reduced-frequency (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…A previous online survey found that 72% of women wanted to know their 10-year risk of breast cancer vs. only 65% for endometrial cancer, 19 and qualitative findings suggest that some women may be more accepting of longer intervals for cervical than breast screening. 11 This could be tested in future studies. We also assessed perceptions of one type of risk assessment (multifactorial).…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 52 women in Australia, participants saw advantages of a multifactorial approach, but had reservations around data security and motivations behind transitioning to this method. 11 There is also varied evidence on women's preferences for delivery of risk assessment results. Research from the United States suggests that women have mixed preferences for written (vs. face-to-face) information, and from primary care clinicians and genetic counsellors, 12,13 whereas participants in a study in Sweden found a consultation with a cancer specialist was most preferable.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a consensus that for risk-based screening to be successfully implemented as part of a population-based screening program, it has to be accepted and supported by stakeholders, particularly women undergoing BC screening [ 11 , 12 ]. Burgeoning evidence from studies conducted in the United Kingdom (UK), Sweden, Netherlands, and Australia [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] indicates that women appear to welcome the prospect of risk-stratified BC screening.…”
Section: Introductionmentioning
confidence: 99%